Disparity in Weekly Number of Co Disparitas jumlah kasus mingguan covid-19 di kabupaten magelang: studi ekologi dengan analisis spasial temporal: Disparity in weekly number of covid-19 cases in magelang regency: ecological study with temporal spatial analysis - Purwoko, Sidiq; Supinganto, Agus; Kusrini, Ina; Musoddaq, Muhamad Arif (Bali Medika Jurnal, 2021)
Magelang Regency is one of the regencies in Central Java whose territory is traversed by the main route between two provinces, namely Central Java Province and DI Yogyakarta Province. This strategic position resulted in high population mobility in the Magelang Regency area, making Magelang Regency the district with the second-highest number of positive Covid-19 cases in 2020 in Central Java Province with 4418 cases after Semarang City. The purpose of this study was to find out a spatial and temporal description of the weekly incidence of new Covid-19 cases at the peak of the 2020 pandemic, namely December. The type of research is quantitative descriptive research with ecological studies using spatial and temporal approaches. The sample is all new cases of Covid-19 during the peak period of cases, namely December 2020. The results show that based on spatial-temporal analysis, it is seen that areas crossed by national transportation routes have a tendency to increase weekly Covid-19 cases in December 2020. dominated by rural areas are sub-districts with a low tendency to add Covid-19 cases.